ISOLATION AND MOLECULAR IDENTIFICATION OF POTENTIALLY PATHOGENIC Escherichia coli AND Campylobacter jejuni IN FERAL PIGEONS FROM AN URBAN AREA IN THE CITY OF LIMA, PERU - Moisés CABALLERO; Isabel RIVERA; Luis M. JARA; Francisco M. ULLOA-STANOJLOVIC; Carlos SHIVA (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
SUMMARY Feral pigeons (Columbia livia) live in close contact with humans and other animals. They can transmit potentially pathogenic and zoonotic agents. The objective of this study was to isolate and detect strains of diarrheagenic Escherichia coli and Campylobacter jejuniof urban feral pigeons from an area of Lima, Peru. Fresh dropping samples from urban parks were collected for microbiological isolation of E. coli strains in selective agar, and Campylobacterby filtration method. Molecular identification of diarrheagenic pathotypes of E.coliand Campylobacter jejuni was performed by PCR. Twenty-two parks were sampled and 16 colonies of Campylobacter spp. were isolated. The 100% of isolates were identified as Campylobacter jejuni. Furthermore, 102 colonies of E. coli were isolated and the 5.88% resulted as Enteropathogenic (EPEC) type and 0.98% as Shiga toxin-producing E. coli (STEC). The urban feral pigeons of Lima in Peru can act as a reservoir or carriers of zoonotic potentially pathogenic enteric agents.